Market timing and selectivity: an empirical investigation of European mutual fund performance - Oliveira, L. (2019)
Using the models proposed by (Treynor & Mazuy, 1966; Henriksson & Merton, 1981), the present study examines the selection and timing abilities of mutual fund managers to denote the practice of these strategies as a means to achieve superior performance. For the 163 European equity mutual funds that followed active management strategies between January 2000 and December 2016, there was no evidence that fund managers used market timing abilities to anticipate the market movements. However, the selectivity component of returns presents slightly positive results, despite the poor overall performance.